Family involvement in geriatric hospitalization: a qualitative analysis of state regulations in Israel - Keren Semyonov-Tal; Eldad Davidov (Israel Journal of Health Policy Research)
Abstract Background The growing recognition of the importance of family involvement in geriatric healthcare underscores the need to examine how regulatory frameworks, such as health regulations, shape family involvement in hospital care. The study’s objectives are twofold. First, it aims to examine how health regulations shape family involvement in geriatric care. Second, the study highlights areas where policies can be adjusted to foster greater family participation. Methods We conducted a qualitative analysis of over 150 regulations related to geriatric care in Israel, focusing on how these regulations facilitate family participation as an organizational goal that could either support or hinder family involvement in the care process. Results Our findings reveal that various government documents largely promote and encourage family involvement to foster a more responsive and effective healthcare system. We identified several key aspects of family participation in geriatric treatment, including information sharing and communication, care planning and decision-making, advocacy, and emotional and social support. This study makes two primary contributions. First, it provides a detailed examination of how regulations strengthen the role of families in the geriatric healthcare environment, thereby reducing organizational overload and enhancing patients’ well-being. Second, it highlights the need for legal reform to better incorporate and integrate family involvement in geriatric care, addressing contradictions between real-world practices and regulatory frameworks to meet the evolving needs of the older population. Conclusions The study offers insights for policymakers and healthcare providers seeking to develop regulatory frameworks that enhance family involvement in geriatric healthcare.